2020
DOI: 10.1038/s41598-020-76152-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extracellular vesicle miRNAs as potential biomarkers of superstimulatory response in cattle

Abstract: The ability to predict superstimulatory response would be a beneficial tool in assisted reproduction. Using small RNAseq technology, we profiled extracellular vesicle microRNA (EV-miRNA) abundance in the blood plasma of heifers exhibiting variable responses to superstimulation. Estrous synchronized crossbred beef heifers (n = 25) were superstimulated and blood samples were collected from each heifer on Day 7 of consecutive unstimulated (U) and superstimulated (S) cycles. A subset of high (H) and low (L) respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Systemic blood flow is a critical supply channel of cellular signalling mediators specifically through sEV, which activates phenotypic changes throughout the entire organ system of an organism 68 , 69 . Plasma EV cargo facilitates critical functions specifically during reproduction and recent studies have identified EV miRNAs as a potential biomarker to identify super-stimulatory response during artificial insemination (AI) of cattle 70 . Nonetheless, proteomic content of circulating plasma exosomes have been identified to distinguish dairy cows with or without uterine infection 71 .Thus, we believe the selection of plasma sEV reflects an excellent cross-section of the physiology of the dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic blood flow is a critical supply channel of cellular signalling mediators specifically through sEV, which activates phenotypic changes throughout the entire organ system of an organism 68 , 69 . Plasma EV cargo facilitates critical functions specifically during reproduction and recent studies have identified EV miRNAs as a potential biomarker to identify super-stimulatory response during artificial insemination (AI) of cattle 70 . Nonetheless, proteomic content of circulating plasma exosomes have been identified to distinguish dairy cows with or without uterine infection 71 .Thus, we believe the selection of plasma sEV reflects an excellent cross-section of the physiology of the dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting group of miRNAs including miR-206, miR-133b, and miR-133a-3p showed a significant up-regulation in the LQ compared to the HQ group. The same three miRNAs exhibited a higher expression pattern in the EVs isolated from the blood plasma of low- compared to high-response heifers to ovarian stimulation [ 47 ]. Both miR-206 and miR-133a are highly correlated with E2 deficiency by targeting and reducing the expression of E2 receptor-α, which mediates the biological activity of E2 in ovarian follicular cells and subsequently affects oocyte quality [ 48 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, three miRNA including bta-miR-655, bta-miR-2285p and bta-miR-2285t were listed as having a target mRNA gene RBBP6 with increased expression in the HF group. While bta-miR-2285p and bra-miR-2285t have been reported to have roles in the bovine estrous cycle ( 61 , 62 ), RBBP6 sperm transcripts were reportedly involved in utero embryonic development ( 63 ). Analysis of the transcripts targeted by the differentially expressed miRNAs showed that five of them (bta-miR-2285p, bta-miR-98, bta-miR-155, and bta-miR-374b, and bta-miR-486) appear to specifically target elements involved in three major biological pathways.…”
Section: Discussionmentioning
confidence: 99%